The Effect of Nimodipine to Reactive Oxygent Species (ROS) in SHSY-5Y Cell-Line Culture Expressed by Chronic Hyperglycemia - Shahdevi NK (Journal of Global Pharma Technology, 2016)
Background: Diabetes mellitus is a metabolic disease with a chronic hyperglycemia condition. Diabetic peripheral neuropathy is a condition that arises from long-term damage due to chronic and hyperglycemia combination of various factors and pathways. One of them is the occurrence of oxidative stress caused by an increase in ROS intracellular. The accumulation of ROS can activate other pathways and result in an ion imbalance Ca2+. Nimodipine is a type L calcium channel blocker which has neuroprotective properties. Therefore, nimodipine is expected to reduce the expression of ROS in neurons that occur due to chronic hyperglycemia conditions. Objective: To determine the effect of nimodipine on ROS in culture of SH-SY5Y-induced cell-line neurons chronic hyperglycemia. Methods: Experimental research with in vitro methods using the exposed SH-SY5Y neuronal cell line chronic hyperglycemia. The study sample was divided into 9 groups, the control normoglycemic group, hyperglycemia control 25 mM and 50 mM, normoglycemia with nimodipine 10 nM and 100 nM, hyperglycemia 25 mM with nimodipine 10 nM and 100 nM, and 50 mM hyperglycemia group with nimodipine 10 nM and 100 nM. Nimodipine is given for 30 minutes on Sh-Sy5Y cells that have previously been exposed to hyperglycemia conditions chronic for 6 days. The intensity of intracellular ROS was observed by immunohistochemical methods on the sixth day. Results: In comparison of normoglycemic conditions (5 mM) and hyperglycemia 25 mM, normoglycemic conditions 5 mM resulting in a significantly higher ROS intensity (p <0.05). Whereas in comparison normoglycemia (5 mM) and hyperglycemia 50 mM had a significant increase in ROS intensity (p <0.05). Expose glucose 5 mM can increase ROS expression due to a series of processes due to hypoglycemic conditions. Exposure to high doses of glucose (50 mM) can increase ROS formation. Giving nimodipine to cells able to reduce the intensity of ROS on glucose exposure 5 mM, 25 mM and 50 mM significantly (p <0.05). Conclusion: Chronic hyperglycemia conditions can increase the formation of ROS in SH-SY5Y and cell cultures nimodipine can significantly reduce ROS levels.Keywords: Nimodipine, SH-SY5Y, ROS, Hyperglycemia, Neuropathy.